Living belief : a short introduction to Christian faith - Ottati, Douglas F. (Grand Rapids, Michigan : : William B. Eerdmans Publishing Company, 2022)
"A leading theologian's concise guide to the beliefs, commitments, and practices of Christianity-organized around the text of the Apostles' Creed, the Ten Commandments, the Sermon on the Mount, and the Lord's Prayer"--
Includes bibliographical references (pages 223-228) and indexes.
Keywords: Theology, Doctrinal -- Popular works